Effect of Mentoring Program on Ways of Coping with Stress and Locus of Control for Nursing Students - Satı Demir, RN, PhD; Sevil Güler Demir, RN, PhD; Hülya Bulut, RN, PhD; Filiz Hisar, RN, PhD (Elsevier, 2014)
Purpose: This study evaluated the effectiveness of a 14-week mentoring program for first year nursing students and their ways of coping with stress and locus of control. Methods: The study was designed as a quasi-experimental study. Sixty-six first year students (mentees) and 66 fourth year students (mentors) were eligible to be in the mentoring program. Mentors and mentees contacted each other weekly, as required, to provide information and support. In order to determine the efficiency of the mentoring program, a Locus of Control Scale, the Ways of Coping Inventory and Mentoring Assessment Form were filled out by mentees. Results: In this study the mentoring program increased students' internal locus of control and active coping with stress. The increase in internal locus of control showed parallelism with students' behaviors of seeking social support. Conclusion: It is recommended that in nursing schools, the mentoring program be used as an additional program.